Strategi Komunikasi Humas Satuan Polisi Pamong Praja Jambi Menjaga Ketertiban Pedagang Kaki Lima - Sartika; Pirhat abbas; Nurhasanah; Mardalina (MAUIZOH: Jurnal Ilmu Dakwah dan Komunikasi, 2019)
This research is motivated by the lack of awareness of street vendors to maintain order, there are still street vendors on Jalan Letjen Haryono Telanipura who sell not in accordance with the regulations they sell during working hours between 06.00 to 16.00 WIB. As a regional regulation enforcement officer, the Civil Service Police Unit in conveying information is assisted by Public Relations in conveying it. From these problems, the authors carried out research to find out the Public Relations Communication Strategy of the Civil Service Police Unit in Maintaining Order for Street Vendors. The research approach that the author uses is qualitative research. to fully explain what happened, using primary and secondary data as the types of data and sources of data obtained through Public Relations (Head of Unit, Head of Sub-Division of General Affairs and Personnel, Section of Public Order) and Street Vendors in Kec. Telanaipura. Data collection techniques were carried out through observation, interviews and also documentation. From the data collection, three data analyzes were carried out in the form of data analysis, in the form of data reduction and data verification. The results of the authors found that the Public Relations Communication Strategy maintains the Order of the Street Vendors, namely: persuasive communication, communication through letters and socialization communication